Novel compound heterozygote mutations of TJP2 in a Chinese child with progressive cholestatic liver disease - Ting Ge; Xinyue Zhang; Yongmei Xiao; Yizhong Wang; Ting Zhang (BMC Medical Genetics, 2019)
Abstract Background Progressive familial intrahepatic cholestasis (PFIC) is a group of genetic autosomal recessive disorders that predominantly affects young children and results in early-onset progressive liver damage. Several types of PFIC were defined based on different genetic aetiologies in last decades. Case presentation Here, we report a Chinese young child diagnosed as PFIC with variants in tight junction protein 2 (TJP2). The patient was affected by a long history of jaundice, pruritus, and failure to thrive. Highly elevated level of serum total bile acid (TBA) and normal levels of gamma-glutamyltransferase (GGT) were observed at hospitalization. The patient’s clinical symptoms could be alleviated by administration of ursodeoxycholic acid. Genetic testing by next generation sequencing (NGS) found novel compound heterozygote mutations c.2448 + 1G > C/c.2639delC (p.T880Sfs*12) in TJP2, which were inherited from her mother and father, respectively. Both mutations were predicted to abolish TJP2 protein translation, and neither has previously been identified. Conclusion We report a Chinese female PFIC child with novel compound heterozygous mutations of TJP2. Genetic testing by NGS is valuable in the clinical diagnosis of hereditary liver disease.